(untitled) (Research, Society and Development, 2021)
Chemistry is a natural science, in which, knowledge is built from facts. Experimental activities allow the student to understand how Chemistry is constructed and developed. Based on this assumption, we sought to investigate the influence and contributions of experimental activities in the process of learning of concepts related to the study of Chemical Solutions. The research included 35 students enrolled in the 2nd grade of high school at a state public school in Colatina-ES in 2019, presenting a methodology with a qualitative and experimental approach. The data were analyzed using the Observational Analysis Method, allowing us to conclude that the use of experimentation in the teaching process can generate incentives to curiosity and research, enhancing the students knowledge.